Studying the efficiency of soil decontamination when using a device with the biosorbent “econadin - Siemaka, Oleksii; Shatokhina, Yulia; Klintsov, Leonid (Eastern-European Journal of Enterprise Technologies, 2018)
We have investigated the efficiency of soil decontamination from petroleum products using the patented perforated device of cylindrical shape with a diameter of 0.04 m, with an area of openings of 0.04 m2, with the biosorbent “Econadin”. the process of soil decontamination lasted over a period of 35 days. Petrol of grade A92 was used as a model pollutant. The present study was conducted in order to improve the process of purification from petroleum products by transporting the biosorbent into deep layers of soil. The result of the study is the established dependence of the concentration of a pollutant (C) in soil on a distance (R) to the device: Ñ=–0.00009134R2–0.001017858R+0.07274845. The dependence, established to control the process of purification, makes it possible to compile methodological recommendations on the use of the proposed device. Based on the Malthus model, combined with a diffusion process, we acquired the data that explain the mechanism of neutralization of gasoline with bacteria located in the examined device. Under the assigned conditions, purification is enabled through the migration of bacteria into soil with a diffusion coefficient D=0.08801 cm2/day and a constant of the natural population growth rate r=0.165168. The obtained results are useful and important to control the process of purification and to devise methodical recommendations on the use of the proposed design. A given approach makes it possible to calculate the neutralization of gasoline at a change in the boundary conditions, for example, a radius of the cylinder of a specialized device with a biosorbent, the limit of distance form it, and the duration of effective utilization of the device. For other soils and pollutants, a combined method has been proposed, including the Malthus method, based on the description of a diffusion process; it could also be applied upon determining the parameters r, D and C0 experimentally